2012
DOI: 10.1177/0748233712442733
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of P53 and CD68 in mouse liver withSchistosoma mansoniinfection and the protective role of silymarin

Abstract: Schistosomiasis is one of the major human parasitic diseases in many developing countries and is one of the causes of morbidity and mortality in the human population. The present work has been planned to study the histopathological and immunohistochemical expression of P53 and CD68 in mouse liver tissues experimentally infected with Schistosoma mansoni, in addition to the ameliorating role of silymarin. A total of 50 adult male mice were divided into 5 groups (10 animals each). Groups 1 and 2 were the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In the immunohistochemical examination for PCNA and P53 proteins, a strong positive reaction in glomeruli and renal tubules were observed in the kidney sections of the Ehrlich carcinoma group according to Tousson et al and Eldaim et al who detected that Ehrlich tumor causes proliferation and apoptosis in renal tissues and induced strong positive expressions in Ki67, P53, and PCNA proteins in the female mice. Also, our results agree with Aldubayan et al who found that Ehrlich tumor‐induced higher expression of PCNA and KI67 proteins that observed in renal and hepatic tissues for mice.…”
Section: Discussionmentioning
confidence: 93%
“…In the immunohistochemical examination for PCNA and P53 proteins, a strong positive reaction in glomeruli and renal tubules were observed in the kidney sections of the Ehrlich carcinoma group according to Tousson et al and Eldaim et al who detected that Ehrlich tumor causes proliferation and apoptosis in renal tissues and induced strong positive expressions in Ki67, P53, and PCNA proteins in the female mice. Also, our results agree with Aldubayan et al who found that Ehrlich tumor‐induced higher expression of PCNA and KI67 proteins that observed in renal and hepatic tissues for mice.…”
Section: Discussionmentioning
confidence: 93%
“…The present study revealed that intramuscular injection of Boldenone in male rats induces a significant elevation in food intake, fluid intake, RBW, and RHW. Tousson et al [ 13 ] demonstrated that the RBW of male rabbits increased significantly following Boldenone injection. Shabir et al [ 33 ] reported a significant increase in food intake, water intake, and weight gain in male rats after Boldenone injection.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were divided into four equal groups (10 each) after 2 weeks of acclimatization: normal control (administered vehicle (sesame oil) injection); positive control or GSPE (GSPE was administered via a stomach tube at 50 mg/kg body weight, twice a week) [ 11 ]; Boldenone (treated with Boldenone undecylenate (5 mg/kg/week, i.m.)) [ 13 ]; and Boldenone then posttreatment with GSPE (treated at the doses and routes mentioned above). Boldenone and vehicle were injected in the hind limbs for 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The present findings need to be considered when immunohistological studies on cryostat or paraffin material from human inflammatory disorders are undertaken, as it is conceivable that a potentially erroneous impression of macrophage-derived damage is present [28][29][30].…”
Section: Inflammatory Cells In Colonic Mucosa Of Ibd Patientsmentioning
confidence: 99%